Difficulties in Pronouncing Arabic Sounds Among Learners of Arabic as a Second Language: A Case Study - Ahmed Amouri, Rania (El Omda in Linguistics and Discourse Analysis, 2018)
The present study investigates the difficulties of Arabic pronunciation encountered by non-native speakers. It has been commonly known that Arabic phonemes are of special features that cannot be grasped easily even by the adults as a second language. This is attributed to the fact that Arabic language – as mother tongue – is impactful on various phonemes such as Ayn العين , H-aa الحاء, R-aa الراء and so on. The current study centralizes Arabic pronunciation difficulties especially that phonemes of special characteristics for non-native learners from Indian origin in particular adopting case study approach. The subjects for the study were two academic employees from AlJouf University, KSA whose age is over forty to examine their ability to pronounce some phonemes and to check how far their native tongues affect their pronunciations. Furthermore, the research focuses upon the pivotal role of practice to correct pronunciation errors. It also highlights the importance of role-play as well as audio-lingual method. [The instruments used were observation, recordings and structured questionnaire and the findings have been tabulated and analyzed statistically and descriptively] The aim of the study is to identify these attributes that are related to some Arabic phonemes to examine whether they can be central characteristics – produced by non-native speakers as if they were systematic rules - of interlanguage or not. The study also analyze if these attributes can later be developed, modified or applied on all language levels except that of the phoneme level